2021
DOI: 10.1093/icb/icab026
|View full text |Cite
|
Sign up to set email alerts
|

Glucocentric Metabolism in Ultra-Endurance Sled Dogs

Abstract: The total energy expenditure of a racing sled dog can exceed 500 kcal/kg bodyweight during typical events spanning a week or more. Based on early research, as well as practical considerations, modern commercial diets are formulated to meet these energy requirements using fat and protein. However, more recent research provides a clear picture of a canine athlete with glucocentric metabolism, including many conditioning-induced adaptations oriented towards sustaining submaximal exercise with glucose as the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The typical conditioning program for ultraendurance sled dog racing has been shown to increase muscle oxidative capacity [ 27 , 28 ] without evidence of fiber type switching (based on myosin ATPase staining) [ 29 ]. Despite a diet that is strikingly high in fat [ 29 , 30 ], conditioning for endurance exercise in these athletes results in a distinct glucocentric metabolic strategy [ 31 ] characterized by high stimulus for hepatic glucose output during exercise [ 32 ] and increased capacity for peripheral glucose clearance [ 9 ]. Increased expression of glucose transporters provide a critical step in support of skeletal muscle utilization of glucose as the preferred substrate for exercise [ 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The typical conditioning program for ultraendurance sled dog racing has been shown to increase muscle oxidative capacity [ 27 , 28 ] without evidence of fiber type switching (based on myosin ATPase staining) [ 29 ]. Despite a diet that is strikingly high in fat [ 29 , 30 ], conditioning for endurance exercise in these athletes results in a distinct glucocentric metabolic strategy [ 31 ] characterized by high stimulus for hepatic glucose output during exercise [ 32 ] and increased capacity for peripheral glucose clearance [ 9 ]. Increased expression of glucose transporters provide a critical step in support of skeletal muscle utilization of glucose as the preferred substrate for exercise [ 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if our observation remains speculative, the kinetics of SCACs could reflect an increase in protein catabolism as SCACs increase in plasma is simultaneous to the decrease in serum globulins previously observed [ 11 ]. It has already been observed that dogs have a high gluconeogenic capacity from precursors as glycerol and lactate (the latter to a small extent) [ 12 , 68 , 69 ], and, probably more importantly, from amino acids [ 70 ]. Circulating amino acids derive either from dietary proteins or from endogenous protein catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating amino acids derive either from dietary proteins or from endogenous protein catabolism. Commercial diets for sled dogs have a high protein content (>25–30%) [ 6 , 70 ]; the increase in serum urea nitrogen concentration observed in sled dogs during multiday exercise [ 11 ] sustains the idea that an important fraction of these proteins is used for gluconeogenesis [ 70 ]. Moreover, a decrease in serum globulin concentration [ 11 ], a loss of body mass and an increase in circulating cortisol have been reported in sled dogs during prolonged multiday exercise [ 1 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletic animals are those that have an overall greater level of physical fitness, measured by VO 2max values that are above average, indicating superior aerobic endurance (Poole et al, 2005). Sled dogs in particular have been noted to burnup to 11,250 kcal/day during long term bouts of exercise, (Davis, 2021, 2023; Hinchliff et al, 1997). As a result, the heat dissipation requirements are so great that, in human athletes, effective thermoregulation is the most pressing challenge during physical activity due to the large number of muscles contracting, and generating heat (El Helou et al, 2012; Lieberman & Bramble, 2007).…”
Section: Introductionmentioning
confidence: 99%